2016
DOI: 10.4103/0259-1162.179310
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative nausea and vomiting: A simple yet complex problem

Abstract: Postoperative nausea and vomiting (PONV) is one of the complex and significant problems in anesthesia practice, with growing trend toward ambulatory and day care surgeries. This review focuses on pathophysiology, pharmacological prophylaxis, and rescue therapy for PONV. We searched the Medline and PubMed database for articles published in English from 1991 to 2014 while writing this review using “postoperative nausea and vomiting, PONV, nausea-vomiting, PONV prophylaxis, and rescue” as keywords. PONV is influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
3
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(78 citation statements)
references
References 66 publications
(107 reference statements)
4
65
3
6
Order By: Relevance
“…[ 17 ] Elevated ICP is also 1 of the risk factors for PONV. [ 18 ] Based on the results of this study, we can expect that TIVA will decrease the elevation of ICP compared to volatile agents and reduce the incidence of PONV in RALP. Additional study is required to elucidate the effects of increased intracranial pressure on PONV in RALP patients.…”
Section: Discussionmentioning
confidence: 91%
“…[ 17 ] Elevated ICP is also 1 of the risk factors for PONV. [ 18 ] Based on the results of this study, we can expect that TIVA will decrease the elevation of ICP compared to volatile agents and reduce the incidence of PONV in RALP. Additional study is required to elucidate the effects of increased intracranial pressure on PONV in RALP patients.…”
Section: Discussionmentioning
confidence: 91%
“…The Apfel simplified risk score is based on four predictors: female, history of PONV and/or motion sickness, nonsmoking status, and use of postoperative opioids [ 33 ]. Roberts et al and Shaikh et al demonstrated that postoperative opioids increased risk for PONV [ 34 , 35 ]. Therefore, we speculate that the signifcant difference in the incidence of nausea between the two groups may result from the different opioid with IV-PCA.…”
Section: Discussionmentioning
confidence: 99%
“…nonpharmacological prophylaxis along with interventions that reduce baseline risk is employed in patients with high PONV risk. [20][21][22] Several studies in the literature report that inability of patients in respect of maintaining their selfcare at home after an outpatient operation is one of the disadvantages of this type of surgical intervention. 2,7,18 In respect of the daily life activities within the first 24 hours in the post-surgery period, our study found that patients had difficulty in walking and moving around, going up the stairs, in meeting their needs with respect to self-care, bathing and dressing-undressing (Table 3).…”
Section: Discussionmentioning
confidence: 99%